Analyzing the Relationship Between Service Quality and Customer Satisfaction in Nepal’s Commercial Banking Sector - Ojha, Shristi Suman (Apex Journal of Business and Management, 2025)
This study examines customers’ perceptions of service quality in Nepalese commercial banks, focusing on five key dimensions: tangibility, reliability, responsiveness, assurance, and empathy. Data collected from customers of ten major commercial banks were analyzed using descriptive statistics, correlation, and regression analysis through SPSS to examine the impact of these dimensions on customer satisfaction. The results reveal that tangibility, reliability, and empathy have a significant positive effect on customer satisfaction, indicating that the physical environment, consistent service delivery, and personalized attention are crucial in shaping customer experiences. Conversely, responsiveness and assurance showed no significant direct impact in the Nepalese banking context. These findings suggest that banks should prioritize improvements in tangibility, reliability, and empathy to enhance customer satisfaction and foster customer loyalty. For bankers, focusing on these key dimensions can lead to stronger customer relationships, increased retention rates, and a competitive advantage in the market. By investing in modern branch facilities, ensuring dependable service, and training staff to provide personalized care, banks can improve overall service quality and drive sustainable growth. Future research could explore additional service quality factors or investigate the indirect effects of responsiveness and assurance on customer satisfaction in the evolving banking landscape.